Enhanced decomposition-based hybrid evolutionary and gradient-based algorithm for many-objective optimization - Mohammad Zadeh, Parviz; Mohagheghi, Mostafa (Applied intelligence (Dordrecht, Netherlands), 2023)
This paper presents a novel decomposition-based hybrid many-objective optimization method using particle swarm optimization (PSO) and sequential quadratic programming (SQP) algorithms. In the proposed method, the objective function space decomposed into optimization sub-problems. In this respect, the origin of the coordinate systems of the scaled objective function space (i.e., ideal point) and uniformly distributed points in the scaled objective function space are used to generate reference directions. The scaling of the objective function space in each generation leads to the improvement of the accuracy of the ideal point, which is important because of its role in the generation of the reference directions. In the proposed method, optimization of all the reference directions performed simultaneously to increase the accuracy as well as the computational efficiency. In addition, the proposed method is based on the hybridization of multi-objective particle swarm optimization (MOPSO) using the reference direction and local fast and accurate search capabilities of the SQP to provide a computationally more efficient and accurate algorithm for solving many-objective optimization problems. In the proposed method, a new mutation operator was introduced into the MOPSO to enhance the computational performance, uniformity of the solution and to prevent the MOPSO from pre-convergence to the local Pareto front. The proposed method was compared with other many-objective optimization algorithms using several challenging DTLZ benchmark problems and real-world many-objective optimization problems involving 3 to 15 objective functions. The results show that the proposed method has a high diversity and very accurate Pareto solutions. In this respect, the proposed method outperforms other recently developed many-objective optimization algorithms used in this study. Based on the obtained results, the proposed method provides an effective way of solving many-objective optimization problems.